Engaging in productive sector development: Comparisons between Mozambique and Ghana - Lars Buur; Lindsay Whitfield (Danish Institute for International Studies (DIIS), 2011)
Through a comparison of sector cases in Mozambique and Ghana, the paper analyzes why and how African states engage in developing productive sectors and with what success. It argues that successful state interventions depend on four factors: (1) sustained political support by the government leadership; (2) the existence of an embedded and mediating bureaucracy; (3) changing the 'rules of the game' which govern the distribution of economic benefits and resources; and (4) the organisation of industry actors and institutionalised interaction between industry actors and state actors. The paper starts with a case of successful intervention in Mozambique, using the four factors to explain why the Mozambican government's efforts to rehabilitate the sugar industry were successful over a fifteen year period. The paper then considers experiences in three sectors in Ghana that illustrate variation in the four factors and thus different economic outcomes. Specifically, cocoa, export is a case of sustained political support, palm oil is a case of poorly implemented industrial policy, and horticulture export is a case of political neglect of an industry. In concluding, the paper emphasizes the political context in which these sector cases are embedded and which shapes how ruling elites make policies and implement them, placing the comparisons within a broader conceptual framework.
Keywords: 300; Entwicklungspolitik; Wirtschaftsförderung; Branchenentwicklung; Produktivität; Mosambik; Ghana